Real time object detection for autonomous AUVs using an attention-based fast-RCNN framework - Boudhane, Mohcine; Toulni, Hamza (Zielona Góra: Uniwersytet Zielonogórski)
This article considers the problem of fish monitoring in an underwater environment, where many problems might occur, including occlusion, pose changes, and complexity of the scene. Recognizing fish behavior is very important to develop various types of technologies able to provide more precise estimations and monitoring of fish populations in a long term.
Keywords: underwater monitoring; deep learning; object detection and identification; AUVs; optical images; underwater robotics; intelligent robots